The Teacher as Guide and Warrior: Metaphors about the Teaching Profession (2020)
In the context of various reforms to the Chilean educational system and the demonstrations that it has provoked, the objective of this investigation is to analyse the metaphorical concepts about the figure of the teacher. In the study we used a qualitative approach and a phenomenological design. 168 Chilean English Teaching students who were in the final years of their undergraduate degree answered an eliciting metaphor questionnaire. The analysis of the metaphorical expressions obtained from the questionnaire was carried out through semantic content analysis. From this analysis, three major categories were defined: metaphors focused on the teacher, metaphors focused on the students and metaphors focused on the teacher’s social recognition. The results show that, even though the subjects are aware of the difficulties of their practice, they have a positive impression of the teaching practice. In parallel, the prevailing idea was that of the teacher as a medium for the learning of his or her students.